2021
DOI: 10.1049/cds2.12051
|View full text |Cite
|
Sign up to set email alerts
|

Effect analysis of small‐problem‐based teaching method for improving students’ problem‐solving ability in the experiment of power electronics course

Abstract: To make students understand the working principle of circuits in the course of Experiment of Power Electronics more deeply, the author introduces a small-problem-based teaching method to help students master the relevant curriculum content and enhance their ability of independent problem-solving within 1 or 2 days for balancing the contradiction between course time and burden. Teachers present some small questions according to the basic principles of circuits, and students analyse the problems theoretically. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…It indicated that changes in assessment type can affect the way students respond. Zhao [11] analyzed the effects of small and medium teaching method problems in the power electronic experiment on improving the effectiveness of the problem-solving ability of students. The study aimed to make students in the power electronic experiment further understand the working principle of the circuit, help students' master relevant course content, and improve their independent problem-solving skills within one to two days for balancing the contradiction between class hours and class burden.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It indicated that changes in assessment type can affect the way students respond. Zhao [11] analyzed the effects of small and medium teaching method problems in the power electronic experiment on improving the effectiveness of the problem-solving ability of students. The study aimed to make students in the power electronic experiment further understand the working principle of the circuit, help students' master relevant course content, and improve their independent problem-solving skills within one to two days for balancing the contradiction between class hours and class burden.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Considering modern approaches to the organization of the educational process, special attention should be paid to distance online learning (D-Learning), which is not a completely new product, but quite a successful and verified by the practice of using information and computer technologies in the educational process of the higher educational establishment (Zhao, 2021).…”
Section: Figure 4 Comparative Assessment Of the Effectiveness Of Usin...mentioning
confidence: 99%
“…The current AC electric power system is a polyphase system that uses three phases in the transmission and distribution system, typically three wires, and four lines with a neutral for customers [1,2]. A smaller wire cross section and better electrical power distribution provided by the use of three phases increase the cost-effectiveness of cable provision [3].…”
Section: Introductionmentioning
confidence: 99%